Sonic and Parametrical Entities in Tetras: An Analytical Approach to the Music of Iannis Xenakis - Harley, James (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 1996)
From his earliest works, Xenakis has conceived his music in terms of textures and sound masses. The analytical approach introduced here for a study of the recent string quartet, Tetras, takes such sonic entities as its point of departure. The inside-time structure is described in terms of the temporal succession of these entities and the outside-time relationships established between them by means of a whole range of parametrical entities. While the sonic and parametrical entities need to be specified for each piece, it is shown that this approach can be profitably applied to the complete Xenakis oeuvre.